Study on Simulation and Experiment of Y-Mo Co-Doped AgSnO2 Contact Materials - Jingqin Wang; Yongqiang Chang; Yancai Zhu; Guangzhi Zhang; Guanglin Huang (Crystals, 2021)
Due to the shortcomings of AgSnO2 as a contact material, models of SnO2, Y-SnO2, Mo-SnO2, and Y-Mo-SnO2 were built to calculate their electrical and mechanical properties based on the first principles of density functional theory. The Y-Mo co-doped SnO2 was the most stable of all the models according to the enthalpy change and the impurity formation energy. By analyzing the energy band structure and the density of states, it was shown that the doped models are still direct bandgap semiconductor materials. The valence band moved up and the conduction band moved down after doping, reducing the band gap and enhancing conductivity. With the reduced energy for carrier transition, the electrical performance of Y-Mo co-doped SnO2 was improved best. The mechanical properties of SnO2 were completely improved by Y-Mo co-doping according to calculation results. The doped SnO2 materials were prepared by the sol-gel method, and the doped AgSnO2 materials were prepared by the powder metallurgy method. X-ray diffraction, hardness, conductivity and wettability experiments were undertaken, with experimental results showing that AgSnO2 can be improved comprehensively by Y-Mo co-doping, verifying the conclusions of the simulation. Overall, the present study provides an effective method for the preparation of high-performance contact materials.